Iowa RBA, September 19-29, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for September 19-29, 1995. Highlights of the update include sightings of a Red Phalarope, Black-legged Kittiwake, Jaeger (species unidentified), Marbled Godwit and three juvenile Sabine's Gulls. Epson - sheet feed/flatbed